2021
DOI: 10.1161/circulationaha.120.053361
|View full text |Cite
|
Sign up to set email alerts
|

Nidogen-2 Maintains the Contractile Phenotype of Vascular Smooth Muscle Cells and Prevents Neointima Formation via Bridging Jagged1-Notch3 Signaling

Abstract: Background: How the extracellular matrix (ECM) microenvironment modulates the contractile phenotype of vascular smooth muscle cells (VSMCs) and confers vascular homeostasis remains elusive. Methods: To explore the key ECM proteins in the maintenance of the contractile phenotype of VSMCs, we applied protein-protein interaction (PPI) network analysis to explore novel ECM proteins associated with the VSMC phenotype. By combining in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 70 publications
1
32
0
Order By: Relevance
“… 246 Jagged1-Notch3 signaling mediates nidogen-2 to maintain the contractile phenotype of VSMCs through in vitro and in vivo. 247 Although abundant studies have identified that Notch has a central role in the control of SMC development and function, and intimal repair, much less is known about its role in the fate of VSMCs in atherosclerotic development and progression. Recent studies demonstrated that Notch signaling is required for the adhesion of VSMCs but not other types of VSMC-derived cells in the formation of the cap in mouse atherosclerosis, and reduction of Notch signaling is a prerequisite for medial VSMC mediating the development of plaque, 248 suggesting that sequential loss and gain of Notch signaling is required for the recruitment of cap SMC population in atherosclerosis.…”
Section: Signaling Pathways In Atherosclerosismentioning
confidence: 99%
“… 246 Jagged1-Notch3 signaling mediates nidogen-2 to maintain the contractile phenotype of VSMCs through in vitro and in vivo. 247 Although abundant studies have identified that Notch has a central role in the control of SMC development and function, and intimal repair, much less is known about its role in the fate of VSMCs in atherosclerotic development and progression. Recent studies demonstrated that Notch signaling is required for the adhesion of VSMCs but not other types of VSMC-derived cells in the formation of the cap in mouse atherosclerosis, and reduction of Notch signaling is a prerequisite for medial VSMC mediating the development of plaque, 248 suggesting that sequential loss and gain of Notch signaling is required for the recruitment of cap SMC population in atherosclerosis.…”
Section: Signaling Pathways In Atherosclerosismentioning
confidence: 99%
“…The discovery that Notch3 regulates PDGFRB links two important signalling pathways in VSMC differentiation and a Notch–PDGF signalling axis may in fact not be restricted only to mural cells, as it was recently observed that a NOTCH3 gain-of-function (NOTCH3 L1519P ) elevated PDGFRB expression in infantile myofibromatosis, a non-metastatic cancer formed in bone, skin and muscle [ 70 ]. Progress is also made in understanding the mechanistic details of Notch3 function in VSMCs, and the basement membrane protein Nidogen-2 was recently found to interact with Jagged1 and stabilize the Jagged1–Notch3 interaction [ 71 ].…”
Section: Notch and Vascular Developmentmentioning
confidence: 99%
“…Nidogen-2 is a basement membrane glycoprotein that enhances the interaction between Jagged1 and Notch3 and subsequent Notch3 activation. Compared with wild-type mice, Jagged1 overexpression attenuated the inhibition of neointima formation in nidogen-2 -/- mice ( 90 ). Cyclic stretch enhances Nox1 mediated ROS production through MEF2B activation signal and causes VSMCs to switch to a synthetic phenotype ( 91 ).…”
Section: Mechanisms Of Vsmcs In Asmentioning
confidence: 99%